GSK-3 Inhibition as a Therapeutic Approach Against SARs CoV2: Dual Benefit of Inhibiting Viral Replication While Potentiating the Immune Response - Rudd, Christopher E. (Frontiers in Immunology, 2020)
The SARS-CoV2 (COVID-19) pandemic and uncertainties in developing a vaccine have created an urgent need for new therapeutic approaches. A key question is whether it is possible to make rational predictions of new therapies based on the presently available scientific and medical information. In this regard, I have noticed an omission in the present analysis in the literature related to the exploitation of glycogen synthase kinase 3 (GSK-3) as a therapeutic approach. This is based on two key observations, that GSK-3 inhibitors can simultaneously block SARs viral replication, while boosting CD8+ adaptive T-cell and innate natural killer (NK) responses. Firstly, it is already clear that GSK-3 phosphorylation of SARs CoV1 N protein on key serine residues is needed for viral replication such that small molecule inhibitors (SMIs) of GSK-3 can inhibit viral replication. In comparing protein sequences, I show here that the key sites in the N protein of SARs CoV1 N for replication are conserved in SARs CoV2. This strongly suggests that GSK-3 SMIs will also inhibit SARs Cov2 replication. Secondly, we and others have previously documented that GSK-3 SMIs markedly enhance CD8+ cytolytic T-cell (CTL) and NK cell anti-viral effector functions leading to a reduction in both acute and chronic viral infections in mice. My hypothesis is that the repurposing of low-cost inhibitors of GSK-3 such as lithium will limit SARS-CoV2 infections by both reducing viral replication and potentiating the immune response against the virus. To date, there has been no mention of this dual connection between GSK-3 and SARs CoV2 in the literature. To my knowledge, no other drugs exist with the potential to simultaneously target both viral replication and immune response against SARs CoV2.